TRADING OF ENERGY CARRIERS: GLOBAL AND DOMESTIC EXPERIENCE - Перевозова, Ірина Володимирівна; Ластовець, Олексій Ігорович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The analysis of reform directions and the current state of the energy market in Ukraine was carried out. It is based on the adaptation of national legislation to international experience and the works of domestic scientists. The energy sector of any country is key in ensuring energy and economic security. Attention is focused on the necessity to reform the energy sector of Ukraine. The strategic goal is integration into the EU and the development of alternative energy sources. Models of the organization of energy markets in the world have been studied. The differences lie in the operation of the wholesale and retail electricity markets and the direct state influence on them. The advantages and disadvantages of each model are determined. The need for the fastest introduction of the deregulation model of wholesale and retail markets in Ukraine is substantiated. The organizational structure of the existing electricity market in Ukraine has been built. Its functional analysis was carried out at the transitional stage of reform. The place and role of traders in this structure are defined. Segments of the wholesale market were studied: forward bilateral contracts, day-ahead, intraday and balancing market. The existing practical experience allowed to investigate the shortcomings of the functioning of the electricity market in Ukraine in recent years. Deficiencies in the work of the National Energy Regulator and the state’s desire to retain influence in the price regulation of tariffs have been clarified. This has a negative impact on the performance of energy generating companies, in particular, to prevent malicious collusion by market participants and financial intermediaries; promote the fastest development of trading, as a key tool in the formation of the financial market, etc. The scientific novelty of this work is the improvement of the domestic experience of the energy market organization based on a critical analysis and shortcomings of the functioning of the existing model, which, unlike the existing ones, connects it with excessive state influence and allows to justify the need for the development of financial instruments and institutions.